Karakteristik Ibu , Aksesibilitas, Keterjangkauan, Dukungan Suami Dan Keluarga, Budaya Dalam Pemilihan Penolong Persalinan Di Wilayah Kerja Puskesmas Kutalimbaru Kabupaten Deliserdang - Zuraidah Zuraidah; Sukaisi Sukaisi (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Selection of birth attendants is a factor that determines the implementation of a safe delivery process. The relationship between the selection of health workers or non-health workers includes education, knowledge, attitudes, accessibility, affordability, husband and family support, culture. In the working area of ??the Kutalimbaru Health Center there are still births assisted by non-health workers due to internal and external factors. . The type of research is an analytical survey with a population of 154 mothers giving birth in the last seven months and 100 mothers giving birth as a sample. Data were obtained through interviews using a questionnaire and analyzed using multiple logistic regression tests. The results showed that attitude (p=0.000), husband and family support (p=0.000) had a significant relationship with the choice of birth attendant. Attitude is the variable that is most related to the selection of birth attendants in the working area of ??the Kutalimbaru Health Center, Deliserdang Regency, with a regression coefficient of 5.305. It is suggested to the head of Kutalimbaru, Deliserdang Regency, to increase programs aimed at inviting the public to give birth to midwives. So that it can increase the mother's good attitude about safe delivery assistance and the husband and family support the selection of health workers as birth attendants